2011
DOI: 10.1111/j.2044-8341.2011.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Therapeutic Assessment for self‐harm in adolescents: Training outcomes

Abstract: TA is a brief intervention associated with improved treatment engagement. TA training is feasible and is associated with improved quality of self-harm assessment. SFBT-based exit is the most commonly used strategy in TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…TA might have lead to improved engagement by addressing the participants’ hopes and expectations from self-harm assessment through an unusual reminder (sending a TA understanding letter) or through improving adolescents’ experience of self-harm assessment. Alternatively, it is possible that spending more time with adolescents (approximately 40 min on average10) and clinicians’ enthusiasm may both have contributed to the increased engagement. In comparison with older similar studies investigating the impact of brief crisis interventions in adolescents presenting with self-harm, the improved engagement was greater yet the study was embedded into routine clinical practice and the intervention was delivered by front-line clinicians with no prior experience of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TA might have lead to improved engagement by addressing the participants’ hopes and expectations from self-harm assessment through an unusual reminder (sending a TA understanding letter) or through improving adolescents’ experience of self-harm assessment. Alternatively, it is possible that spending more time with adolescents (approximately 40 min on average10) and clinicians’ enthusiasm may both have contributed to the increased engagement. In comparison with older similar studies investigating the impact of brief crisis interventions in adolescents presenting with self-harm, the improved engagement was greater yet the study was embedded into routine clinical practice and the intervention was delivered by front-line clinicians with no prior experience of research.…”
Section: Discussionmentioning
confidence: 99%
“…Main strengths of the study include pragmatic design and using an intervention with minimal training requirements10 delivered by front line clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Once school assessment took place, the RT and CCST will invite the family, patient and possibly teacher to the office to discuss the results and offer therapeutic assessment (TA, a method by Ougrin et al, [26]) as first intervention. TA consists of a joint construction of a diagram (based on a cognitive analytic therapy paradigm) that consists of three elements: reciprocal roles, core pain and maladaptive behavioural patterns, which are each assumed to play a crucial role in setting off and promoting dysfunctional cycles of behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Cooper, Lezotte, Jacobellis, and Diguiseppi () found that suicide attempts were significantly fewer in Colorado counties with a combination of crisis response, case management, mental health treatment, and community education. Ougrin, Zundel, Ng, Habel, and Latif () concluded from a review of randomized controlled trials that services that engage parents, schools, peers, and communities result in reduced attempts compared with hospitalization for adolescent clients.…”
Section: Shores: a Supported Mnemonicmentioning
confidence: 99%